2011
DOI: 10.1103/physrevb.84.205431
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale magnetic study of Ni(111) and graphene on Ni(111)

Abstract: We have investigated the magnetism of the bare and graphene-covered (111) surface of a Ni single crystal employing three different magnetic imaging techniques and ab initio calculations, covering length scales from the nanometer regime up to several millimeters. With low temperature spinpolarized scanning tunneling microscopy (SP-STM) we find domain walls with widths of 60 -90 nm, which can be moved by small perpendicular magnetic fields. Spin contrast is also achieved on the graphene-covered surface, which me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 40 publications
13
44
0
Order By: Relevance
“…The total induced spin moment in graphene is very small (≈0.01μ B per unit cell of graphene), and it is interesting to note that it is oriented antiparallel to the Co-ML moment. Note that similar spin magnetic moments at the C atoms are reported for graphene/Ni(111) [43]. Let us compare our data with previously reported graphene/Co/Ir(111) calculations by Decker et al [23].…”
Section: Electronic Structure Calculationssupporting
confidence: 89%
“…The total induced spin moment in graphene is very small (≈0.01μ B per unit cell of graphene), and it is interesting to note that it is oriented antiparallel to the Co-ML moment. Note that similar spin magnetic moments at the C atoms are reported for graphene/Ni(111) [43]. Let us compare our data with previously reported graphene/Co/Ir(111) calculations by Decker et al [23].…”
Section: Electronic Structure Calculationssupporting
confidence: 89%
“…In both cases, the CoCp 2 molecule attains a nominal S=1/2 spin. The small lattice mismatch (1.2%) of graphene and Ni(111) lattice constant results in pseudomorphic growth and the flat conformation of the graphene layer [25]. DFT calculations have shown that the bonding between graphene and the Ni(111) surface is primarily due to van der Waals (vdW) interactions [26], with a binding distance of ∼2.1Å, in good agreement with experiments [27].…”
supporting
confidence: 66%
“…24,31,32 In the STM image of a (1 Â 1) domain there is a notable asymmetry between the two different sublattices due to influence of the Ni(111) surface atoms. Simulations of the graphene/Ni(111) STM images 24,33 demonstrate that the sublattice H, which is located above the hollow sites of the Ni(111) surface (see Figure 3b), must appear higher than the sublattice T, located above the Ni atoms. This allows us to determine the positions of the topmost Ni atoms in the STM images (see blue circles in Figure 3a).…”
Section: Resultsmentioning
confidence: 99%